Designing, managing and supporting construction projects through innovation and IT solutions - Proceedings of the World IT Conference for Design and Construction (2004 : Langkawi, Malaysia); Brandon, Peter; Heng, Li; Noridah Shafii (Kuala Lumpur : Construction Industry Development Board Malaysia, 2004)
03